2000
DOI: 10.1073/pnas.200357097
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocopherol and its major metabolite, in contrast to α-tocopherol, inhibit cyclooxygenase activity in macrophages and epithelial cells

Abstract: Cyclooxygenase-2 (COX-2)-catalyzed synthesis of prostaglandin E 2 (PGE2) plays a key role in inflammation and its associated diseases, such as cancer and vascular heart disease. Here we report that ␥-tocopherol (␥T) reduced PGE2 synthesis in both lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages and IL-1␤-treated A549 human epithelial cells with an apparent IC 50 of 7.5 and 4 M, respectively. The major metabolite of dietary ␥T, 2,7,8-trimethyl-2-(␤-carboxyethyl)-6-hydroxychroman (␥-CEHC), also exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
320
1
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(355 citation statements)
references
References 52 publications
25
320
1
9
Order By: Relevance
“…In an effort to determine the effects of membrane soluble N 2 O 3 quenchers on the csPDI-dependent RSNO inf lux, HUVECs were grown in the presence of 10 M ␣-tocopherol for 14 h. Jiang et al (18) have reported that under these conditions epithelial cells were able to accumulate Ϸ0.9 nmol of ␣-tocopherol͞10 6 cells, which translates to a membrane concentration of Ϸ5 mM. The rates of intracellular DnsHCys quenching by the extracellular introduction of 25 M BSA-NO then were compared in ␣-tocopherol-treated and control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to determine the effects of membrane soluble N 2 O 3 quenchers on the csPDI-dependent RSNO inf lux, HUVECs were grown in the presence of 10 M ␣-tocopherol for 14 h. Jiang et al (18) have reported that under these conditions epithelial cells were able to accumulate Ϸ0.9 nmol of ␣-tocopherol͞10 6 cells, which translates to a membrane concentration of Ϸ5 mM. The rates of intracellular DnsHCys quenching by the extracellular introduction of 25 M BSA-NO then were compared in ␣-tocopherol-treated and control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…a-TC reduces both prostaglandin-E2 production by macrophages and pro-inflammatory cytokine synthesis and secretion by activated macrophages and monocytes (Capuron et al 2009). c-TC also reduces prostaglandin E2 synthesis by even greater inhibition in cyclooxygenase (COX)-2 activity in macrophages, as well as reducing COX-2 activity in epithelial cells ( Jiang et al 2000). Safety data and dosing for vitamin E is as yet unclear for different human populations.…”
Section: Effects On Inflammation and Relation To Mood Changesmentioning
confidence: 99%
“…All of the subsequent experiments were performed in the presence of 1% FBS unless otherwise indicated. Because cyclooxygenase and lipoxygenase are believed to promote tumorigenesis (24-26), we decided to investigate whether the antiproliferation effect of ␥T is due to its inhibition of these enzymes (7,8). Although the presence of low micromolar concentrations of AA and LA, the substrates of cyclooxygenase and lipoxygenase, partially reversed the inhibitory effect of ␥T (Fig.…”
Section: ␥T Inhibited Proliferation Of Several Cancer Cell Lines But mentioning
confidence: 99%
“…Recently, studies by us and others have indicated that other forms of vitamin E appear to have unique properties that are not shared by ␣T but may be important to human health (6). For instance, ␥T, the major form of vitamin E in U.S. diets, but not ␣T, exhibits anti-inflammatory activities by inhibiting cyclooxygenasecatalyzed prostaglandin E 2 formation in cell cultures and animals (7,8). ␥T, unlike ␣T, is strongly nucleophilic and thus is more efficient than ␣T in trapping reactive nitrogen species (9)(10)(11).…”
mentioning
confidence: 99%